Answer:
Option 2nd and 3rd are correct.
The solutions to f(x) =g(x) are;
x = -2 and x = -1
Step-by-step explanation:
Let x represents the independent variable and f(x) and g(x) represents the dependent variable.
Given the function:
and
\
we have to find the solution to f(x) = g(x).
From the given table you can see that:
For x = - 2
f(-2) = 4
g(-2) = 4
then;
f(x) = g(x) for x = -2
Also;
For x = - 1
f(-1) = 2
g(-1) = 2
then;
f(x) = g(x) for x =-1
Therefore, the solutions to f(x) =g(x) are, x = -1 and -2